LIQUIDITY OF A COMMERCIAL BANK: THEORETICAL ASPECT - NIKOLCHUK, Yuliya; SHVABII, Kostiantyn; KASYANOV, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The relevance of the research topic is justified by the fact that the liquidity of a commercial bank is the main basis for ensuring its financial stability and reliability. The bank’s liquidity is a guarantee of the normal functioning of the national banking system and a high level of trust in it on the part of the population and business entities. The article examines the approaches to defining the concept of "bank liquidity" existing in the scientific literature. To date, science has formed three approaches to determining bank liquidity, namely: as a bank’s ability to fulfill its obligations, as a ratio between the relevant groups of assets and liabilities of banking institutions, and as a process of converting assets into means for repaying own obligations. Both at the legislative level and in scientific literature, the first approach gained the most popularity. Some researchers believe that when studying bank liquidity, it is also necessary to determine the liquidity of the banking system, the liquidity of the bank’s balance sheet, and the liquidity of the bank’s assets and liabilities. It was determined that the world banking practice provides for a separate consideration of the bank’s liquidity as a "reserve" and as a "flow". The first approach involves comparing asset stocks with the need for liquid assets. The second approach involves taking into account the bank’s ability to attract liquid resources in case of need. The essence of determining bank liquidity was studied by comparing appropriately grouped assets with liabilities. It was determined that bank liquidity is under the constant influence of external and internal factors, which must be taken into account during its management. The essence of the main problem of bank liquidity is summarized. Bank management must constantly make a choice between ensuring a stock of liquid assets and reducing their profitability, or increasing the bank’s profitability with a decrease in the stock of liquid assets. The topic of further research will be the modern methodology of liquidity management of commercial banks.